Mursamacin: a novel class of antibiotics from soil-dwelling roundworms of Central Kenya that inhibits methicillin-resistant Staphylococcus aureus [version 2; referees: 2 approved, 1 approved with reservations] - Ryan Musumba Awori; Peter Njenga Ng'ang'a; Lorine Nanjala Nyongesa; Nelson Onzere Amugune; Daniel Masiga (F1000Research, 2017)
Antibiotic-resistant bacteria, also called “superbugs”, can at worst retrogress modern medicine to an era where even sore throats resulted in death. A solution is the development of novel types of antibiotics from untapped natural sources. Yet, no new class of antibiotic has been developed in clinical medicine in the last 30 years. Here, bacteria from insect-killing Steinernema roundworms found in the soils of Central Kenya were isolated and subjected to specific molecular identification. These were then assayed for production of antibiotic compounds with potential to treat methicillin-resistant Staphylococcus aureus infections. The bacteria were identified as Xenorhabdus griffiniae and produced cell free supernatants that inhibited S. aureus. Fermenting the bacteria for 4 days yielded a heat stable anti-staphylococcal class of compounds that at low concentrations also inhibited methicillin-resistant S. aureus. This class contained two major compounds whose identity remains unknown. Thus X. griffinae isolated from Steinernema roundworms in Kenya have antimicrobial potential and may herald novel and newly sourced potential medicines for treatment of the world’s most prevalent antibiotic resistant bacteria.